A polyoxometalate-encapsulated nanocage cluster organic framework built from Cu4P2 units and its efficient bifunctional electrochemical performance. Issue 96 (20th November 2020) - Li, Shaobin; Tan, Xiaoguo; Yue, Ming; Zhang, Li; Chai, Dongfeng; Wang, Wendi; Pan, Hong; Fan, Linlin; Zhao, Chunyan
Abstract : The first polyoxometalate-encapsulated twenty-four-nucleus organophosphorus-copper nanocage cluster organic framework has been constructed and it is shown to exhibit highly efficient bifunctional electrochemical performance. Abstract : The first polyoxometalate (POM)-encapsulated twenty-four-nucleus organophosphorus-copper nanocage cluster organic framework has been constructed. Here, the phosphomolybdate POMs were incorporated into an octahedral nanocage cluster organic framework, and the resulting material exhibited highly efficient bifunctional electrochemical performance. The crystalline material showed a high specific capacitance of 366.3 F g −1 at a current density of 3 A g −1 .